拉盖尔-高斯光束照射产生散斑场的特性研究 = Study on properties of speckle field formed by Laguerre-Gaussian beam illumination - 李新忠 Li Xinzhong (2018)
研究了拉盖尔-高斯光束照射毛玻璃产生的散斑场的特性。利用空间光调制器结合计算全息法产生了拉盖尔-高斯涡旋光束；较深入地研究了拉盖尔-高斯光束照射下散斑大小与光束径向指数、角向指数及涡旋光束面积间的关系。结果显示：对同一径向指数，散斑颗粒平均大小随角向指数的增大呈直线减小趋势；对同一角向指数，散斑大小随径向指数的增大而减小；散斑大小与涡旋光束照射面积的负指数成正比；随径向指数的增大，其逐渐接近高斯光束照射的结果。 The properties of speckle field is studied when Laguerre-Gaussian (LG) beams illuminate a ground glass plate. The LG vortex beams are generated by a spatial light modulator combing with computer-generated hologram. The relation of speckle size and azimuthal and radial indices and the bright region of the LG beams are analyzed experimentally. Experimental results show that the speckle size decreases linearly with the azimuthal index increasing for certain radial index. Similarly, the speckle size also decreases with the radial index increasing for certain azimuthal index. Moreover, the speckle size is proportional to the negative factor of illuminating area of the LG beam. Further, the negative factor is gradual close to the results of Gaussian beam illuminating with the increasing radial index.